2012
DOI: 10.1111/j.1461-9563.2012.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

New primary resource increases predation on a pest in a banana agroecosystem

Abstract: Primary resources may affect the structure of species assemblages in upper trophic levels of food webs. These bottom-up effects may involve important ecological processes that affect pest control. For example, population densities of natural enemies may increase when alternative preys are favoured by a new resource. 2 Ants, particularly Solenopsis geminata Forel (Myrmicinae), are recognized as effective predators of herbivores eggs. In the present study, we tested the hypothesis that the addition of a primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…An increase in plant diversity can contribute to an increase in the abundance of predators by providing a broader range and greater abundance of prey (Mollot et al. ), of nectar sources, and of suitable microclimates (Landis et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in plant diversity can contribute to an increase in the abundance of predators by providing a broader range and greater abundance of prey (Mollot et al. ), of nectar sources, and of suitable microclimates (Landis et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…), and banana plantations (Mollot et al. ). In the case of herbaceous annual crops, most options involve the integration field margins and the management of hedgerows (Marshall and Moonen ; Gaba et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symondson et al (2002) reported that ants are predators of Lepidoptera, and Pfannenstiel (2005) observed ants feeding on H. zea eggs. We also expected to find Solenopsis geminata (Fabricius) in our sweet corn plots since our study site was the same as that used for a study by Mollot et al (2012) on the banana weevil, in which S. geminata was abundant, and the species is commonly found on corn (Litsinger et al 2007). Holway et al (2002) reported that S. geminata is a predator of Lepidoptera and so we expected it to be a predator of H. zea in the sweet corn plots.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope signa-tures can be used directly using natural differences in the isotopic abundances in the landscape, or in enrichment studies, where isotope-labeled supplements are added to the system. Natural abundance studies use naturally occurring differences in isotopic signatures to follow flows and processes (Hood-Nowotny & Knols, 2007;Girard et al, 2011;Mollot et al, 2012). For example, prey origins and colonization behavior of the lady beetle Hippodamia convergens (Gu erin-M eneville) in agricultural systems were examined by analysis of carbon stable isotope values (Prasifka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%